2021
DOI: 10.3390/en14175446
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Advancement in the LED Lighting Technologies on the Optimum Windows-to-Wall Ratio of Jordanians Residential Buildings

Abstract: Based on recent developments and the predicted future advancement of lighting technologies, researchers are now questioning the extent to which daylight is effective in lowering the overall energy consumption of buildings. As light-emitting diode (LED) luminaires are highly energy efficient, the amount of power consumed for lighting purposes can be reduced, even in situations where the lighting system is at its full power. It has already been demonstrated that LED-lighting technologies can facilitate significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The final screening process yielded 41 relevant studies in the AMM countries, with 32 studies found in Mashreq countries and 9 in Maghreb countries, as shown in Figure 7. In the Mashreq countries, there were 18 studies in Jordan [64,65,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84], 9 in Egypt [85][86][87][88][89][90][91][92][93][94], 2 in Palestine [95,96], 2 in Iraq [97,98], 1 in Lebanon [99], and no study was presented for Syria. In the Maghreb countries, there were 5 studies in Algeria [100][101][102][103][104], 3 in Morocco [105][106][107], 1 in Tunisia [67], and no study was presented for Libya.…”
Section: Resultsmentioning
confidence: 99%
“…The final screening process yielded 41 relevant studies in the AMM countries, with 32 studies found in Mashreq countries and 9 in Maghreb countries, as shown in Figure 7. In the Mashreq countries, there were 18 studies in Jordan [64,65,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84], 9 in Egypt [85][86][87][88][89][90][91][92][93][94], 2 in Palestine [95,96], 2 in Iraq [97,98], 1 in Lebanon [99], and no study was presented for Syria. In the Maghreb countries, there were 5 studies in Algeria [100][101][102][103][104], 3 in Morocco [105][106][107], 1 in Tunisia [67], and no study was presented for Libya.…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of solar irradiance through the wall is much smaller compared to the window; at the same time, the solar light can be used to light the room. The windowsto-wall ratio should be optimised to minimise both heating and cooling loads, as well as the total energy consumed by lighting while maintaining a suitable lighting level for occupants [35]. The work hour variable is also an important predictor because it deals with daily work schedules, but it is substantially connected with NoM and NoF.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of local research, on the one hand, numerous studies have been conducted to investigate energy consumption for both new and existing residential buildings in Jordan, such as [18,[37][38][39][40][41][42][43][44][45]. However, most of these studies focused on improving indoor comfort levels and increasing the energy efficiency in residential buildings.…”
Section: Literature Reviewmentioning
confidence: 99%